Assessment of Intersection Capacity at Persiaran Pulai Perdana - Ismail, Muhammad Hamizan; Ab. Ghani, Ahmad Raqib (Recent Trends in Civil Engineering and Built Environment, 2025)
This study analyzes the operational performance of the four intersections along Jalan Persiaran Pulai Perdana in Johor during peak hours in 2023. Researchers meticulously measure traffic volume in both morning and evening peak periods, using SIDRA version 8 for data analysis. The current 4-leg intersection exhibits movement issues in most lanes, leading to inefficiency and congestion, with researchers studying Level of Service (LOS) F for potential improvements. To optimize future traffic flow, enhancing capacity and LOS for most lanes is crucial, prioritizing strategic enhancements for congestion relief. Adopting these strategies ensures a more streamlined and effective transportation system, promising a convenient travel experience. If a flyover replaces the current four-way intersection, LOS could improve from F to a more favorable A or B grade. This planning initiative is driven by time constraints, emphasizing the urgent need to address road challenges. The project aims to benefit Majlis Bandaraya Iskandar Puteri (MBIP) by enhancing traffic management along Jalan Persiaran Pulai Perdana, leading to a more efficient and safer transportation system.